Reflexions sobre la vocal temàtica - Sifre, Manuel (Caplletra. Revista Internacional de Filologia, 1995)
The stem vowel in Catalan verbs is a formative which is adjoined to the verbal base in order to constitute the verbal stem. Both the processes of inflection and of derivation act upon the verbal stem. This essay analyzes the function of the vowel stem and its allomorphic distribution, as well as the consequences of this distribution. In addition, in view of pairs of verbs such as aterrar and aterrrir, the conclusion reached is that the stem vowel cannot be considered to afford any lexical meaning. On the other hand, it is able to make a word into a verb. This behaviour is typically derivative, and it is not the only case. In spite of this, it also partakes in inflectional properties, for which reason the article upholds that the distinction between inflection and derivation cannot be radical, but gradual.